The Comparison of Cooperative Learning Model Viewed from Students’ Emotional Intelligence - Ahmad Junaedi; Budiyono Budiyono; Isnandar Slamet (Universitas Sebelas Maret, 2017)
This research aimed to know the different influence of each learning model, emotional Intelligence, and interaction between those two elements toward the students’ achievement in mathematic. This is an experimental study within the 3x3 factorial design. The populations of this study were VII grade students of State Junior High Schools (SMP) in Surakarta city in academic year of 2016/2017. The samples of this study were students of SMPN 8 Surakarta, SMPN 16 Surakarta, and SMPN 20 Surakarta which were taken by stratified cluster random sampling. The instruments to collect the data were achievement test, questionnaire and documentation. The technique to analyze the data was variance analysis of two ways with different cell. Based on the result, it can be concluded that: (1) TGT model produced the same good result as well as TAI model, TGT model produced the better achievement than the direct learning, and TAI model produced the better achievement than direct learning in the algebra material. (2) Students having high emotional intelligence are better than students having low and medium emotional intelligence in term of achievement in mathematics. The students having medium emotional intelligence are as low as students having low emotional intelligence in term of achievement in algebra material. (3) In each category of emotional intelligence, TGT model produced higher achievement than TAI model and direct learning model, TAI and direct learning model produced the equal result in algebra material. (4) In each learning model, students’ achievement of those who have high emotional intelligence are higher than those who have medium and low emotional intelligence, and students who have low and medium intelligence produced the equal achievement in algebra material.